IDENTIFIKIASI AMFETAMINE, MARIJUANA DAN MORFIN PADA URINE SISWA SMA “X” DENGAN RAPID DIAGNOSTIC TEST - I Ketut Buana Yasa; Didik Setiawan; M.Adreng Pamungkas (Bali Medika Jurnal, 2017)
Introduction: High rates of drug abuse, especially Amfetamine, Marijuana dan Morfin in Indonesia, including vulnerable areas where circulation is the island of Bali. One of which is the area of Badung, where the victims and targets of drug dealers are adolescents aged 11-24 years. drug should be used for treatment and research, But for various reasons. Drug addicts have been abused. The reasons this research is to identify compounds amfetamine, marijuana and morfin in the urine high school students of class XI language in “X” district of Badung with a rapid diagnostic test. Method: used in this research rapid diagnostic test. Samples were taken through the draw of 2 classes, each 0f which was taken 16 people to obtain 32 urine samples,result from 32 urine samples with a total of 12 women, the number of mem as many as 20 people aged 16-18. With the acknowledgment of not taking drugs. Result: obtained 100% absence amfetamine, marijuana and morfin on the urine sample. Discussion: School advised always to provide guidance on how to avoid the use of drugs to students and parents.